Nursing interventions in adverse reactions in cancer patients using immunotherapy: A scoping review (Research, Society and Development, 2021)
This study aims to map the scientific evidence on nursing interventions related to the management of adverse reactions in adult oncology patients using immunotherapy in the outpatient setting. This is a scoping review, based on the JBI methodology. The population of adult and elderly oncology patients using immunotherapy was used as a strategy, in the concept of nursing interventions in the administration and control of adverse reactions of injectable immunotherapies, with the outpatient setting (PCC) as the context, in line with the JBI guidelines for scoping review. Twenty-three articles were selected, with publications between 2005 and 2020. Three aspects were evidenced for discussion: Nursing interventions in relation to patient/family health education using immunotherapeutics, nursing interventions related to the application of immunotherapeutics to the patient and related interventions adverse reactions after the application of immunotherapeutics. It is evident how much it is necessary the physical examination performed by the nurse and pharmacological knowledge about immunotherapeutics. It is suggested that the systematization of nursing care is present in health institutions, and that institutional protocols are developed to facilitate the professional nursing practice in immunotherapy.